2014
DOI: 10.1115/1.4026360
|View full text |Cite
|
Sign up to set email alerts
|

The Role Of Extracellular Matrix Elasticity and Composition In Regulating the Nucleus Pulposus Cell Phenotype in the Intervertebral Disc: A Narrative Review

Abstract: Intervertebral disc (IVD) disorders are a major contributor to disability and societal health care costs. Nucleus pulposus (NP) cells of the IVD exhibit changes in both phenotype and morphology with aging-related IVD degeneration that may impact the onset and progression of IVD pathology. Studies have demonstrated that immature NP cell interactions with their extracellular matrix (ECM) may be key regulators of cellular phenotype, metabolism and morphology. The objective of this article is to review our recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 102 publications
4
79
0
Order By: Relevance
“…Indeed, a prior study by our group has suggested that NP cells prefer attachment to and matrix synthesis upon very soft substrates of ~ 200 Pa stiffness, although those substrates contained laminin-PEG composite hydrogels, rather than HA-PEG as used here [57]. Also, our other prior studies [71, 78] have also demonstrated that soft (<700 Pa), laminin-containing extracellular matrix substrates promote a biosynthetically active and juvenile NP cell phenotype, as measured by NP cell morphology, cell-cell interactions, and proteoglycan production in vitro. Surprisingly, the results in the current study suggest that softer hydrogels formed from HA-PEG were found to be the least favorable substrates for promoting high matrix synthesis as measured by sGAG/DNA and for both cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a prior study by our group has suggested that NP cells prefer attachment to and matrix synthesis upon very soft substrates of ~ 200 Pa stiffness, although those substrates contained laminin-PEG composite hydrogels, rather than HA-PEG as used here [57]. Also, our other prior studies [71, 78] have also demonstrated that soft (<700 Pa), laminin-containing extracellular matrix substrates promote a biosynthetically active and juvenile NP cell phenotype, as measured by NP cell morphology, cell-cell interactions, and proteoglycan production in vitro. Surprisingly, the results in the current study suggest that softer hydrogels formed from HA-PEG were found to be the least favorable substrates for promoting high matrix synthesis as measured by sGAG/DNA and for both cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Much work has been done in the field to study NP cell characteristics in IVD tissue of various species, specifically how NP cell characteristics change with age (with matrix elasticity values from 0.3 up to 5 kPa 11,26,27 ). Juvenile NP cells have been characterized via the presence of brachyury-T 44 and production of extracellular matrix molecules (aggrecan, type II collagen, and laminin β 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, loss of NP proteoglycan matrix coupled with an increased content of nonaggregating proteoglycan breakdown products attenuates the hygroscopic properties of ECM, resulting in reduced water content, swelling pressure and ability to withstand load. Dehydration of the NP also inhibits the availability of nutrients and growth factors to the disc cells, leading to further impairment of IVD function [28].…”
Section: Matrix Synthesis and Degradation During Disc Degenerationmentioning
confidence: 99%